Heterogeneity and excitability of BRAFV600E-induced tumors is determined by Akt/mTOR-signaling state and Trp53-loss. Issue 5 (1st December 2021) - Cases-Cunillera, Silvia; van Loo, Karen M J; Pitsch, Julika; Quatraccioni, Anne; Sivalingam, Sugirthan; Salomoni, Paolo; Borger, Valeri; Dietrich, Dirk; Schoch, Susanne; Becker, Albert J
Abstract: Background: Developmental brain tumors harboring BRAF V600E somatic mutation are diverse. Here, we describe molecular factors that determine BRAF V600E -induced tumor biology and function. Methods: Intraventricular in utero electroporation in combination with the piggyBac transposon system was utilized to generate developmental brain neoplasms, which were comprehensively analyzed with regard to growth using near-infrared in-vivo imaging, transcript signatures by RNA sequencing, and neuronal activity by multielectrode arrays. Results: BRAF   V600E expression in murine neural progenitors elicits benign neoplasms composed of enlarged dysmorphic neurons and neoplastic astroglia recapitulating ganglioglioma (GG) only in concert with active Akt/mTOR-signaling. Purely glial tumors resembling aspects of polymorphous low-grade neuroepithelial tumors of the young (PLNTYs) emerge from BRAF V600E alone. Additional somatic Trp53 -loss is sufficient to generate anaplastic GGs (aGGs) with glioneuronal clonality. Functionally, only BRAF V600E / p Akt tumors intrinsically generate substantial neuronal activity and show enhanced relay to adjacent tissue conferring high epilepsy propensity. In contrast, PLNTY- and aGG models lack significant spike activity, which appears in line with the glial differentiation of the former and a dysfunctional tissue structure combined with reduced neuronal transcript signatures in the latter. Conclusion: mTOR-signaling and Trp53 -loss critically determine the biological diversity and electrical activity of BRAF V600E -induced tumors.